Assessment of the thermal performance of plastering mortars within controlled test cells - Kheradmand, Mohammad (2014)
Phase Change Materials (PCM) can be incorporated into plastering mortars in order to improve their thermal properties by exploiting latent heat storage of PCMs. As a consequence, plastering mortars that incorporate PCMs can be applied advantageously to building façades/partitions for improved thermal comfort levels while reducing the overall energy consumption for heating/cooling. The assessment of plastering mortars with Phase Change Materials (PCMs) is experimentally investigated in this paper, aiming to assess the effectiveness of the PCM into the mortar, here termed as single PCM plastering mortar (SPCMM). In order to demonstrate the effectiveness of the PCM mortar concept, two experiments have been performed. Two small-scale cubic test cells have been constructed, with outer edge of 26 cm and inner edge of 20 cm. In regard to the outer lining of these two cells, the following applies: one of them was externally lined with conventional mortar (here termed as REFM); and another lined with single PCM plastering mortar. The cells were closed, placed inside climatic chambers and subjected to realistic temperature scenarios in South European countries, whereas the inner temperature was continuously recorded. It was shown that a smoother indoor temperature profile is obtained when PCMs are implemented. An improvement in human comfort can thus be anticipated.